Lycia isabellae (Harrison, 1914) (Geometridae) in Xestia sexstrigata (Haworth,1809) (Noctuidae) - novi vrsti v favni metuljev Slovenije (Lepidoptera) - Sukič, Milan (Acta entomologica slovenica (Ljubljana), 2007)
Additional two Lepidoptera species: Lycia isabellae (Harrison, 1914) and Xestia sexstrigata (Haworth, 1809), were found for the first time in Slovenia.L. isabellae was discovered as a pupa on the ground beside an old larch tree at the end of winter in 2001 in Zgornje Jezersko. One female hatched from this pupa in February. X. sexstrigata was found in NE Slovenia inthe hilly Goričko region near Grad. One male was caught on light on August 17, 2002.
Keywords: entomologija; metulji; nove vrste; Slovenia; Slovenija